Identification and characterization of a small molecule inhibitor of WNT signaling in glioblastoma cells - De Robertis, Alessandra (2013)
Glioblastoma multiforme (GBM) is the most common and prognostically unfavorable form of brain tumor. The aggressive and highly invasive phenotype of these tumors makes them among the most anatomically damaging human cancers with a median survival of less than one year. Although canonical WNT pathway activation in cancers has been historically linked to the presence of mutations involving key components of the pathway (APC, β-CATENIN or AXIN proteins), an increasing number of studies suggest that elevated WNT signaling in GBM is initiated by several alternative mechanisms that are involved in different steps of the disease. Therefore, inhibition of WNT signaling may represent a therapeutically relevant approach for GBM treatment. After the selection of a GBM cell model responsive to WNT inhibition, we set out to develop a screening approach for the identification of compounds capable of modulating canonical WNT signaling and associated proliferative responses in GBM cells. Here we show that the small molecule SEN461 inhibits the canonical WNT signaling pathway in GBM cells, with relevant effects at both molecular and phenotypic levels in vitro and in vivo. These include SEN461-induced AXIN stabilization, increased β-CATENIN phosphorylation/degradation, and inhibition of anchorage-independent growth of human GBM cell lines and patient-derived primary tumor cells in vitro. Moreover, in vivo administration of SEN461 antagonized WNT signaling in Xenopus embryos and reduced tumor growth in a GBM xenograft model. These data represent the first demonstration that small molecule-mediated inhibition of WNT signaling may be a potential approach for GBM therapeutics.